Nanoformulations targeting immune cells for cancer therapy: mRNA therapeutics - Wei Yang; Jianwei Cao; Hui Cheng; Liang Chen; Meihua Yu; Yu Chen; Xingang Cui (Bioactive Materials, 2023)
The approved worldwide use of two messenger RNA (mRNA) vaccines (BNT162b2 and mRNA-1273) in late 2020 has proven the remarkable success of mRNA therapeutics together with lipid nanoformulation technology in protecting people against coronaviruses during COVID-19 pandemic. This unprecedented and exciting dual strategy with nanoformulations and mRNA therapeutics in play is believed to be a promising paradigm in targeted cancer immunotherapy in future. Recent advances in nanoformulation technologies play a prominent role in adapting mRNA platform in cancer treatment. In this review, we introduce the biologic principles and advancements of mRNA technology, and chemistry fundamentals of intriguing mRNA delivery nanoformulations. We discuss the latest promising nano-mRNA therapeutics for enhanced cancer immunotherapy by modulation of targeted specific subtypes of immune cells, such as dendritic cells (DCs) at peripheral lymphoid organs for initiating mRNA cancer vaccine-mediated antigen specific immunotherapy, and DCs, natural killer (NK) cells, cytotoxic T cells, or multiple immunosuppressive immune cells at tumor microenvironment (TME) for reversing immune evasion. We highlight the clinical progress of advanced nano-mRNA therapeutics in targeted cancer therapy and provide our perspectives on future directions of this transformative integrated technology toward clinical implementation.